Utilities theoretical and practical approach to social networking in Social Work - Garcia Escobar, Jorge (2011)
Social complexity against which capabilities and options facing the professional social worker to drive the constant search for theoretical references and methodological expertise and enable an effective action in the task of social development management. The task and possibilities is constantly challenged multiproblem social realities in that sense social work stands as a social science discipline with integrated approaches and contributions from various academic disciplines but also in a specialized practice contrasted knowledge and skills to the extent that the practice itself will serve to recognize theories and methodologies useful or not for the purpose of qualitatively superior social transformation sought by social Workers. In this respect the present paper presents an approach will generic uses and possibilities that have been attributed over the years to the social network approach in social work, seeks to present in a sense linking scenic and Historic both now but rather old with this approach new impetus in the social sciences in recent years.